RELOKASI SISTEM PANEL SURYA UNTUK KEPERLUAN POMPA AIR DI PANTAI GRIGAK GUNUNG KIDUL - Sumarno, Linggo; Suwarno, Djoko Untoro; Iswanjono, Iswanjono; Martanto, Martanto (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Grigak Beach community experiences difficulty obtaining clean water, especially during the dry season. The lack of duration of the solar panel system that powers the water pump in the drilled well is the cause. Therefore, an effort was made to relocate the solar panel system from the previous location to a new location, which allows the solar panel system to have a longer lifespan. The community service that was carried out successfully relocated the solar panel system from the old location to the new one. The solar panel system can have a lifespan of about two hours longer.